PENGARUH SUMBER INFORMASI DAN PARITAS TERHADAP KEMAUAN IBU MELAKUKAN SENAM NIFAS DINI - Windarti, Yunik; Dewi, Uke Maharani (Universitas Tribhuwana Tunggadewi, 2019)
Gymnastics is not new in the world of health. This activity is very useful to help restore the condition of the mother's body after childbirth to recover as before becoming pregnant. But there are still many postpartum mothers who don't do postnatal exercise. The research objective is to analyze the effectiveness of information sources and parity on the willingness to do early puerperal gymnastics. Design analytical cross-sectional, the sample of postpartum mothers in the Inpatient Primary Clinic of RBG RZ Surabaya for 2 months was taken using a total sampling of 31 respondents. Collecting primary data in the form of questionnaires, then analyzed using multiple logistic regression test. The results showed of the 16 respondents who did not get the information source most (56.3%) did not want to do early puerperal gymnastics and out of 23 multipara respondents, almost all (78.3%) wanted to do early puerperal gymnastics. Partially the source of information (p = 0.016) is effective in influencing the willingness to do puerperal exercise with an OR value of 24, 290 (95% CI: 1,811 - 325,759). Parity (p = 0.070) is not effective against the willingness to do postnatal exercise with a value of OR 9.159 (95% CI: 0.836 - 100.301). The Conclusion providing good information will affect mothers to do postpartum exercise early, but the number of maternal parity does not contribute to the willingness of mothers to do early puerperal gymnastics. .